The makeover reality television and reflexive audiences - Sender, Katherine (New York University Press, 2012)
Watch this show, buy this product, you can be a whole new you! Makeover television shows repeatedly promise self-renewal and the opportunity for reinvention, but what do we know about the people who watch them? As it turns out, surprisingly little. The Makeover is the first book to consider the rapid rise of makeover shows from the perspectives of their viewers. Katherine Sender argues that this genre of reality television continues a long history of self-improvement, shaped through contemporary media, technological, and economic contexts. Most people think that reality television viewers.
Keywords: Reality television programs -- History and criticism.; Makeover television programs -- History and criticism.; PERFORMING ARTS -- Television -- Reference.; Makeover television programs.; Reality television programs.; Televisie.; Reality-TV.; Kijkgedrag.; Electronic books.; Criticism, interpretation, etc.